THE EFFECT OF PRODUCT QUALITY, SERVICE QUALITY AND PRICES ON CONSUMER SATISFACTION OF MOLIVIA CAFE (Case Study on Consumers of Molivia Cafe, Jalan H.M. Joni, Teladan Timur, Medan City) - Slamet Widodo (Institute of Computer Science (IOCS), 2021)
This research is about customer satisfaction of Molivia Cafe. The phenomenon that occurs in this study is that there was a decrease in sales in 2019 due to complaints from consumers who felt that the quality of the products provided was not appropriate or still normal, there were some facilities that did not function according to their benefits, and consumers also still complained about prices that were not appropriate. with perceived benefits. This study aims to determine the effect of product quality, service quality, and price on consumer satisfaction Molivia Cafe, where the independent variables are: Product Quality (X1), Service Quality (X2), and Price (X3), the dependent variable is: Consumer satisfaction (Y). The population in this study were all consumers of Molivia Cafe with a sample of 97 respondents. The analytical model used is Multiple Linear Regression which is processed using the SPSS version 20 application program, data is collected using a questionnaire that has been filled out by Molivia Cafe consumers. This analysis includes: Validity Test, Reliability Test, Multiple Linear Regression Analysis, Classical Assumption Test, Hypothesis Testing through T Test and F Test and Coefficient of Determination (R2). Based on the results of this study indicate that product quality has a positive and significant effect on consumer satisfaction, service quality has a negative and statistically significant effect on consumer satisfaction, and price has a positive and significant effect on consumer satisfaction. The Coefficient of Determination of Adjusted R Square shows that 45.3% of the variation in consumer satisfaction can be explained by the three independent variables and the remaining 54.7% is influenced by other variables outside the research model, such as location, advertising and others.